Correction algorithm of migration through Doppler cells for space target in bistatic ISAR - Bao-feng GUO; Chao-xuan SHANG; Xin WANG; Jun-tao MA; Jian DONG (Tongxin xuebao)
Aiming at the problem of migration through Doppler cells in bistatic ISAR,based on bistatic ISAR turntable model,the reason of migration through Doppler cells from two aspects of echo model and the relative speed changes of scattered points was analyzed.The correction algorithm was presented based on range cell phase compensation.Firstly,target rotating rate was estimated through the geometrical relationship of bistatic stations and target.Secondly,the algo-rithm divided the echo data into two parts,and then imaging separately,getting two images of different angles of view.And the rotating center was estimated according to the maximum criterion of rotating correlation,which was used to range scaling.The migration through Doppler cells was corrected through phase compensation of each range cell at last.The simulation result show that the method could solve the problem of migration through Doppler cells,and could im-prove the image quality.